In Bundelkhand... Profit maximization with horticultural crops - Singh, V K; Singh, S K; Shukla, K C; Dubey, Amiraj (Indian Horticulture, 2018)
Prem Lal Yadav, an innovative farmer from Tikamgarh district has emerged as successful farmer by introducing horticultural crops in his traditionally wheat etc. grown crop belt. He has taken advantage of technological intervention in his area. He adopted greenhouse like latest technology and diversified the entire land with horticultural crops.